Analysis of thermal comfort in traditional architecture, focused on digital simulations - Bustán-Gaona, Darío (2024)
Indexed keywords Sustainable Development Goals SciVal Topics Abstract Traditional Ecuadorian architecture refers to structures whose technical and visual characteristics date from pre-Columbian times to the mid-20th century. However, such architectural interventions can still be found in the Andean region, mainly in remote villages away from urban centers. Among the architectural features, ancestral knowledge passed down through generations and a construction system based on mud, wattle and daub, adobe, and other materials. The analysis aims to develop thermoenergetic simulations to identify the thermal comfort of buildings in Pilahuin Parish Center (Ambato, Ecuador). The methodology is based on a qualitative and quantitative approach, and using non-probabilistic random sampling, the following main variables were analyzed: geographic orientation, type of layout, building height, materiality, and number of floors. After surveying and architectural drawing of the buildings, 3D models were developed using Autodesk REVIT software. Consequently, digital three-dimensional architectural models were imported into Design Builder software. This process generated a diagnosis of the current state of the buildings in terms of habitability, based on interior thermal comfort. The results showed an average indoor air temperature of 18.77°C and an average relative humidity of 50.76%. With this data, strategies were developed to improve habitability based on Olgyay's theory of architecture and climate. The resulting data, also obtained in Design Builder, allowed for a proposal to achieve the average indoor air temperature and relative humidity within the optimal ranges of Olgyay's theory and the Ecuadorian Construction Standard. Therefore, by making certain material changes while respecting their heritage value, thermal discomfort levels were improved by 27.67% compared to the analyzed interior temperature, thereby enhancing the quality of life for the inhabitants.